Projetos educativos no Instituto de pesquisas Jardim Botânico do Rio de Janeiro: uma prática de sensibilização para concientização ambiental - Rodrigues, Milena Goulart Souza (2005)
The study proposed to investigate the activities that promote environmental reflection in the Botanical Garden Research Institute of Rio de Janeiro, which offers a place of interaction with nature that is important for the development of non-formal education. It is an alternative place to learn and to teach nature preservation, offering a favorable environment for the implementation of educative practices that lead the public to reflect over relevant questions such as the environment. This study emphasized in its theoretical part, the relation of the Brazilian environment questions and the education in the Botanical Garden of Rio de Janeiro. This can be used, especially to contribute with the conservation / preservation of the environment as well as to help overcome the main local environmental problems. To collect data, it was used a form directed to the visitors and filled by the researcher, internal document analysis and observations of three educative projects developed in the institution. The study focused on the activities of sensitization through the process of environmental perception, aiming the change of habits and attitudes of the visitors of the Garden. Therefore it presented a concern in divulging complex questions such as ethics, social values, and economic questions in the sustainability context.